A CRITICAL ANALYSIS OF NATURAL RESOURCES IN MURSHIDABAD DISTRICT: A CASE STUDY - Haque, Sakila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Murshidabad, a historically significant district of West Bengal, is endowed with diverse natural resources such as fertile alluvial soil, abundant water bodies, and agricultural biodiversity. Despite its ecological wealth, the region faces severe challenges due to unsustainable exploitation, mismanagement, and policy neglect (Chatterjee, 2020). This study critically examines the availability, utilization, and degradation of natural resources in Murshidabad, highlighting the socio-economic consequences of their mismanagement. The primary objective of this research is to assess the current state of natural resources in the district, identify key environmental and institutional challenges, and propose sustainable solutions for their conservation and equitable use. The study also explores the community's dependence on natural resources and evaluates the governance mechanisms in place. Methodologically, the research adopts a mixed-method approach. It combines secondary data from government reports, satellite imagery, and environmental surveys with primary data collected through field interviews and stakeholder consultations in selected Gram Panchayats. The key findings reveal a critical depletion of water tables, illegal sand mining along the Bhagirathi river, shrinking forest cover, and soil degradation in several agricultural blocks (Banerjee & Das, 2019; Bose, 2021). Additionally, there exists a significant gap between environmental policies and grassroots-level implementation, further exacerbated by climate variability and weak institutional accountability.